Toward a new faculty materialising the move - Ezihaslinda, Ngah (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
2-3 Nov 2009. A group of CMLHS associates gathered at Bukit Gambang Resort, Gambang Kuantan to discuss details and come up with documentation for a presentation before a group of expert panelists in a workshop held at the Grand Seasons Hotel, Kuala Lumpur on 6 to 8 November 2009.